Mechanism of rare earth element neodymium (Nd) affecting photosynthesis of oil seed rape (Brassica napus L.) - WEI You-zhang (浙江大学学报. 农业与生命科学版, 2000)
Concentration of leaf chlorophyll, rate of photosynthesis and Mg2+-ATPase activity on chloroplast membrane of oil seed rape (Brassica napus L.) treated with different concentrations of Nd(NO3)3 (3, 6 and 60 μmol·L-1) were measured. Ultrastructure of leaf cell was also observed with TEM (transmission electronic microscopy) after Nd(NO3)3 treatment. Photosynthesis was enhanced by low concentration of Nd(NO3)3 of 3 μmol·L-1. In contrast, high concentration of Nd(NO3)3 of 60 μmol·L-1 inhibited photosynthesis. It is concluded that the effect of Nd on chloroplast structure and Mg2+-AT-Pase activity on chloroplast membrane result in Nd affecting photosynthesis of oil seed rape.